Mechanical and corrosion characteristics of TiC reinforced Ni-P based nanocomposite coatings - Mohammad Farhan (17017683) (2023)
The requirement for effective corrosion protection and better mechanical properties in various industries employing metal components has led to the growth of nickel (Ni)-based metallic coatings. The electroless-synthesized nickel-phosphorus (Ni-P) nanocomposite has emerged as a particularly promising preference among other metallic coatings. This research investigates the mechanical and electrochemical performance of Ni-P coatings reinforced with titanium carbide (TiC) nanoparticles at various concentrations (0.25, 0.50, 0.75, and 1 g/L) of TiC nanoparticles. The evaluation of structural and topographical modifications caused by TiC nanoparticles introduced in the coating bath was carried out employing XRD, FE-SEM/EDS elemental mapping, and AFM techniques. Comprehensive assessments through microhardness and nanoindentation results reveal significant enhancements in mechanical properties. Additionally, erosion studies performed at various impact angles provided valuable insights into crater geometry as well as resistance against erosion. Furthermore, the highest hardness value of 665 HV0.05 was achieved at the composition of Ni-P-0.75TiC as well as electrochemical impedance spectrometry analysis shows a remarkable corrosion inhibition efficiency of 96.6% and potentiodynamic polarization inhibition efficiency of 97.99% as compared to the carbon steel substrate. As a result of their exceptional mechanical performance and good corrosion resistance, Ni-P-TiC nanocomposite coatings can be valuable options across many applications requiring adequate corrosion resistance and superior mechanical properties. Other Information Published in: Materials Today Communications License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.mtcomm.2023.106901